Sister Carrie : The Pennsylvania Edition - Dreiser, Theodore, 1871-1945 (The University of Pennsylvania Dreiser Edition, 1981)
Hidden under layers of error and corruption, the original version of Sister Carrie has finally emerged. The editors of this new edition have gone back to the original handwritten manuscript as well as to the typescript that went to the publisher to restore the text.